Transport Properties of Monolayer MoS2 Grown by Chemical Vapor Deposition - Schmidt, Hennrik; Wang, Shunfeng; Chu, Leiqiang; Toh, Minglin; Kumar, Rajeev; Zhao, Weijie; Castro Neto, A. H; Martin, Jens; Adam, Shaffique; Özyilmaz, Barbaros; Eda, Goki (Nano letters, 2014)
Recent success in the growth of monolayer MoS2 via chemical vapor deposition (CVD) has opened up prospects for the implementation of these materials into thin film electronic and optoelectronic devices. Here, we investigate the electronic transport properties of individual crystallites of high quality CVD-grown monolayer MoS2. The devices show low temperature mobilities up to 500 cm2 V–1 s–1 and a clear signature of metallic conduction at high doping densities. These characteristics are comparable to the electronic properties of the best mechanically exfoliated monolayers in literature, verifying the high electronic quality of the CVD-grown materials. We analyze the different scattering mechanisms and show that the short-range scattering plays a dominant role in the highly conducting regime at low temperatures. Additionally, the influence of optical phonons as a limiting factor is discussed.